The modeling of the composition and properties of functional materials based on polytetrafluoroethylene - Berladir, K.V.; Hovorun, T.P.; Bilous, O.A.; Baranova, S.V. (Functional Materials, 2018)
Design and creation of new structures of three-component antifriction composite materials are based on the researches modeling their behavior in the conditions of tension. In the presented models the uniform approach based on the variation principles of mechanics of a solid body and allowing formulating boundary value problems in the form of a condition of minimality of functionality is used. The multifactoriality of the dependence of wear of a composite on its elasticity, viscoplasticity and durability is considered. Macroscopic characteristics of composite material are directly connected with its structure which is characterized by spatial distribution of components and their properties.